CK2α Deletion in the Hematopoietic Compartment Shows a Mild Alteration in Terminally Differentiated Cells and the Expansion of Stem Cells - Rajesh Rajaiah; Muhammad Daniyal; Marudhu Pandiyan Shanmugam; Hannah Valensi; Koby Duke; Katherine Mercer; Morgann Klink; Matthew Lanza; Yasin Uzun; Suming Huang; Sinisa Dovat; Chandrika Gowda Behura (Cells, 2025)
Casein Kinase II (CK2) is a ubiquitously present serine/threonine kinase essential for mammalian development. CK2 holoenzyme is a tetramer with two highly related catalytic subunits (α or α’) and two regulatory ß subunits. Global deletion of the α or β subunit in mice is embryonically lethal. We and others have shown that CK2 is overexpressed in leukemia cells and plays an important role in cell cycle, survival, and resistance to the apoptosis of leukemia stem cells (LSCs). To study the role of CK2α in adult mouse hematopoiesis, we generated hematopoietic cell-specific CK2α-conditional knockout mice (Vav-iCreCK2 f/f). Here we report the generation and validation of a novel mouse model that lacks CK2α in the hematopoietic compartment. Vav-iCreCK2α f/f mice were viable without dysmorphic features and showed a mild phenotype under baseline conditions. In Vav-iCreCK2α f/f mice, the blood count showed a significant decrease in total red blood cells and platelets. The spleen was enlarged in Vav-iCreCK2α f/f mice with evidence of extramedullary hematopoiesis. HSC and early progenitor cell compartments showed expansion in CK2α-null bone marrow, suggesting that the absence of CK2α impaired their proliferation and differentiation. Given the established roles of CK2 in cell cycle regulation and the findings reported here, further functional studies are warranted to investigate the role of CK2α in HSC self-renewal and differentiation. This mouse model serves as a valuable tool for understanding the role of CK2α in normal and malignant hematopoiesis.